Assessment of nursing care-associated predictors of in-hospital mortality in the patients with acute ischemic stroke - Škodrić, Angelina; Marić, Gorica; Jovanović, Dejana; Beslać-Bumbaširević, Ljiljana; Kisić-Tepavčević, Darija; Pekmezović, Tatjana (Vojnosanitetski pregled, 2021)
Background/Aim. Stroke remains one of the leading causes of death and disability worldwide. The aim of the study was to determine the nursing care-associated predictors of in-hospital mortality in the patients with acute ischemic stroke (AIS) who were hospitalized at the Department of Emergency Neurology. Methods. Prospective cohort study included 59 consecutive patients with AIS admitted to the Department of Emergency Neurology, Neurology Clinic, Clinical Center of Serbia, Belgrade. The patients were followed until discharge or death. For exploring a relationship between the outcome of patients with AIS and different groups of factors, the univariate and multivariate Cox proportionate hazard regression models were used. Results. There were 32 male and 27 female patients with AIS. The mean age was 62.5 ± 15.2 years. The average duration of hospitalization was 11.1 ± 9.6 days (median 8 days; range 1–54 days). Almost 80% of patients (47/59; 79.7%) were admitted to the stroke unit, while 12 (20.3%) patients were admitted to the intensive care unit. In the univariate Cox regression analysis the significant variables (p
Keywords: stroke; mortality; nursing care; nursing; convalescence.